2006
DOI: 10.1194/jlr.m600084-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Krabbe disease: psychosine-mediated activation of phospholipase A2 in oligodendrocyte cell death

Abstract: Globoid cell leukodystrophy (Krabbe disease) is an inherited neurological disorder caused by the pathogenomic accumulation of psychosine (galactosylsphingosine), a substrate for the deficient enzyme galactocerebroside bgalactosidase. This study underscores the mechanism of action of psychosine in the regulation of oligodendrocyte cell death via the generation of lysophosphatidylcholine (LPC) and arachidonic acid (AA) by the activation of secretory phospholipase A2 (sPLA2). There was a significant increase in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(133 citation statements)
references
References 79 publications
5
122
2
Order By: Relevance
“…Interestingly, in this current study, although psychosine alone had no effect on pro-inflammatory cytokine levels, it augmented the LPS-induced release of IL6 from mouse astrocytes, with a similar trend for the levels of TNFα and IL1β. This finding is comparable to those reported previously where psychosine potentiated LPS-induced production of TNFα, IL6, IL1β and NO in primary rat astrocytes, which in turn was suggested to induce oligodendrocyte cell death (Giri et al, , 2006. These enhanced levels of cytokines were reduced by pFTY720, in agreement with previous studies from our and other groups demonstrating that S1PRs play a role in regulating the levels of cytokines in a number of immune and glial cells (Choi et al, 2011;Sheridan and Dev, 2012;Wang et al, 2007;Zhang et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Interestingly, in this current study, although psychosine alone had no effect on pro-inflammatory cytokine levels, it augmented the LPS-induced release of IL6 from mouse astrocytes, with a similar trend for the levels of TNFα and IL1β. This finding is comparable to those reported previously where psychosine potentiated LPS-induced production of TNFα, IL6, IL1β and NO in primary rat astrocytes, which in turn was suggested to induce oligodendrocyte cell death (Giri et al, , 2006. These enhanced levels of cytokines were reduced by pFTY720, in agreement with previous studies from our and other groups demonstrating that S1PRs play a role in regulating the levels of cytokines in a number of immune and glial cells (Choi et al, 2011;Sheridan and Dev, 2012;Wang et al, 2007;Zhang et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…Inflammatory molecules, such as AMP-activated protein kinase (AMPK), prostaglandin D, inducible nitric oxide synthase (iNOS) and pro-inflammatory cytokines have all been implicated in Krabbe disease as well as in the twi/twi mouse animal model of this disease (Giri et al, 2008). Taken together, this increasing evidence now suggests that the loss of oligodendrocytes and widespread demyelination seen in Krabbe disease is due to apoptotic processes as well as aberrant inflammatory response (Giri et al, 2008(Giri et al, , 2006Haq et al, 2003;Tohyama et al, 2001).…”
Section: Introductionmentioning
confidence: 80%
“…Thus, abnormal sphingolipid catabolism or accumulation in lipid microdomains might result in a cell autonomous defect accounting for GLD hematopoietic stem cells compromised functionality (i.e., proliferation, migration, and maturation). Furthermore, because psychosine directly deregulates some specific protein kinase C isozymes (Hannun and Bell, 1987), activates phospholipase A2 (Giri et al, 2006), and modifies mitochondrial membrane potential (Tapasi, 1998) and peroxisomal activity (Khan et al, 2005), its accumulation within thymic stromal tissue or in T cells might also directly interfere with cell survival. Of note, a recent study reported that psychosine favors proinflammatory cytokine secretion by peripheral blood mononuclear cells derived from Krabbe patients (Formichi et al, 2007;Pasqui et al, 2007).…”
Section: Cell Autonomous and Epigenetic Mechanisms Contributing To Immentioning
confidence: 99%
“…The lack of insulation leads to slower signaling which can be measured in a nerve conduction study [101]. A simple model of Krabbe disease can be obtained from the MO3.13 cell line [102,103]. These cells are immortalized oligodendrocytes.…”
Section: Krabbe Diseasementioning
confidence: 99%